Effect of Brown Manuring and Herbicides on Growth, Nitrogen Uptake and Weed Dynamics in Direct Seeded Rice (Oryza sativa L.) - Kumari, Sneha; Kaur, Tarundeep (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was conducted at Department of Agronomy, PAU, Ludhiana. The twelve treatments were rice sole (without herbicide, pendimethalin 750 g ha-1 as PRE, bispyribac 25 g ha-1 as POST and pendimethalin 750 g ha-1 fb bispyribac 25 g ha-1), rice+Sesbania (Brown manuring (BM) of Sesbania at 4 WAS, pendimethalin 750 g ha-1 and BM of Sesbania at 4 WAS, BM of Sesbania at 4 WAS and bispyribac 25 g ha-1 and pendimethalin 750 g ha-1 and BM of Sesbania at 4 WAS and bispyribac 25 g ha-1) and rice+Sesbania (BM of Sesbania at 5 WAS, pendimethalin 750 g ha-1 and BM of Sesbania at 5 WAS, BM of Sesbania at 5 WAS and bispyribac 25 g ha-1 and pendimethalin 750 g ha-1 and BM of Sesbania at 5 WAS and bispyribac 25 g ha-1). Rice with Sesbania, knockdown at 4 and 5 WAS recorded less weed density as compared to sole rice. Integrated use of rice+Sesbania (BM of Sesbania at 4 WAS) with pendimethalin 750 g ha-1 fb post-emergence bispyribac 25 g ha-1 recorded significantly higher biological yield than all other combinations of BM and herbicides. The nitrogen content in paddy grains and straw was not influenced significantly by different brown manuring treatments. N content and uptake in weeds was significantly higher in sole rice under unsprayed check as compared to all other treatment combinations which were at par with each other. Nitrogen uptake in paddy grains was influenced significantly by different brown manuring treatments which varied from 40.12 to 56.22 kg ha-1. N uptake in straw was significantly higher with rice+BM (4 WAS) in pendimethalin fb bispyribac.